Going Beyond Bacteria: Uncovering the Role of Archaeome and Mycobiome in Inflammatory Bowel Disease - Houshyar, Yashar; Massimino, Luca; Lamparelli, Luigi Antonio; Danese, Silvio; Ungaro, Federica (Frontiers in Physiology, 2021)
Inflammatory Bowel Disease (IBD) is a multifaceted class of relapsing-remitting chronic inflammatory conditions where microbiota dysbiosis plays a key role during its onset and progression. The human microbiota is a rich community of bacteria, viruses, fungi, protists, and archaea, and is an integral part of the body influencing its overall homeostasis. Emerging evidence highlights dysbiosis of the archaeome and mycobiome to influence the overall intestinal microbiota composition in health and disease, including IBD, although they remain some of the least understood components of the gut microbiota. Nonetheless, their ability to directly impact the other commensals, or the host, reasonably makes them important contributors to either the maintenance of the mucosal tissue physiology or to chronic intestinal inflammation development. Therefore, the full understanding of the archaeome and mycobiome dysbiosis during IBD pathogenesis may pave the way to the discovery of novel mechanisms, finally providing innovative therapeutic targets that can soon implement the currently available treatments for IBD patients.